2013
DOI: 10.1111/vox.12115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 6 years of confidential unit exclusion at the Belgian Red Cross Flanders Blood Service

Abstract: Although CUE use is associated with higher rates of TTI risk, CUE has low efficiency to detect window period donations. Moreover, misuse results in a significant loss of units. Our data indicate a low risk perception among donors, hence efforts should focus on improving donor knowledge of and on donor's responsibility to disclose TTI risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Despite this issue, the IBTO has used this system to improve the safety of blood and its components [15,24]. Several studies confirmed that CUE is a relatively costbeneficial system that can significantly improve the safety of blood products [15,25]. In our study, this issue was observed and the CUE option was more commonly used by first-time donors.…”
Section: Discussionmentioning
confidence: 64%
“…Despite this issue, the IBTO has used this system to improve the safety of blood and its components [15,24]. Several studies confirmed that CUE is a relatively costbeneficial system that can significantly improve the safety of blood products [15,25]. In our study, this issue was observed and the CUE option was more commonly used by first-time donors.…”
Section: Discussionmentioning
confidence: 64%
“…During the study period, four window period donations detected by HIV‐NAT only were from non‐CUE users indicating a good performance of the Brazilian HIV‐NAT test. Previous studies have shown both low sensitivity and predictive value of CUE to identify window period donations . These non‐CUE users window period HIV cases suggest that the donors might had been concerned in using the CUE‐option and not having their blood tested, overcoming all the blood bank screening barriers in order to donate blood and getting tested.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have shown association of CUE and higher prevalence of serologic markers, however with low sensitivity and positive predictive value to indicate window period of TTI . CUE was discontinued in most US blood centers, while in the recent decade it has been reported in Brazil, Belgium and Canada . The controversy about the utility of CUE usage has increased especially after the implementation of highly sensitive and specific nucleic acid tests (NAT), which reduce, the risk of transmission during the window period .…”
mentioning
confidence: 99%
“…Most of these have not focused on the quality of CUE processes and only compared the donors opting for CUE and those without CUE regarding the serological markers. [9132122] Nevertheless, comparison of HIV prevalence between CUE and non-CUE donors is difficult due to the very low prevalence rate of HIV among blood donors. [9132122] A previous study showed that the prevalence of HBV, HCV, and HIV was higher among the CUE donors.…”
Section: Discussionmentioning
confidence: 99%
“…[9132122] Nevertheless, comparison of HIV prevalence between CUE and non-CUE donors is difficult due to the very low prevalence rate of HIV among blood donors. [9132122] A previous study showed that the prevalence of HBV, HCV, and HIV was higher among the CUE donors. [23] In another previous study, the prevalence of HIV antibody was 21 folds higher among the blood donors who had opted for CUE compared to those who had not.…”
Section: Discussionmentioning
confidence: 99%